2022
DOI: 10.1063/5.0080332
|View full text |Cite
|
Sign up to set email alerts
|

Laser control of a dark vibrational state of acetylene in the gas phase—Fourier transform pulse shaping constraints and effects of decoherence

Abstract: We propose a methodology to tackle the laser control of a non-stationary dark ro-vibrational state of acetylene (C2H2), given realistic experimental limitations in the 7.7 μm (1300 cm−1) region. Simulations are performed using the Lindblad master equation, where the so-called Lindblad parameters are used to describe the effect of the environment in the dilute gas phase. A phenomenological representation of the parameters is used, and they are extracted from high-resolution spectroscopy line broadening data. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 119 publications
(140 reference statements)
0
13
0
Order By: Relevance
“…39 On the dynamical perspective, the couplings lead to the IVR processes. 40 Alike in Aerts et al, 31 we consider here the N s = 0, N r = 2 polyad near 1330 cm -1 , namely the ν 4 + ν 5 band which includes two zero-order states: the bright |0001…”
Section: Structural Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…39 On the dynamical perspective, the couplings lead to the IVR processes. 40 Alike in Aerts et al, 31 we consider here the N s = 0, N r = 2 polyad near 1330 cm -1 , namely the ν 4 + ν 5 band which includes two zero-order states: the bright |0001…”
Section: Structural Parametersmentioning
confidence: 99%
“…Vibrational eigenstates show complex dynamics that is a combination of the underlying zero-order states motions. The numerical values of the Hamiltonian matrix used in this study can be found in the Supplemental material of Aerts et al 31 and the energetic structure of the rovibrational states involved in the dynamics described below are illustrated in Fig. 1.…”
Section: Structural Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The MIR ultrashort pulsed lasers can be widely used in gas detection [7,8], cancer diagnosis [9][10][11], pollutant monitoring [12][13][14][15][16], food quality control [17][18][19][20][21][22][23], and other aspects [24][25][26][27][28], since they own much broader spectral ranges than ultrafast lasers in visible and near-infrared region. In addition, they also play essential roles in strong-field physics [29][30][31][32][33][34], laser surgery [35][36][37][38][39][40][41], attosecond science [42,43], and molecule dynamics [44][45][46] (as shown in Figure 1b), as they feature the ultrashort time domain and have the potential to achieve peak powers. Therefore, there is an essential and broad application value in MIR ultrashort pulse generation research.…”
Section: Introduction 1motivations For the Research Of The Mid-infrar...mentioning
confidence: 99%